2009
DOI: 10.1021/la803562e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Thermodynamics of Adsorption on Hydroxyapatite of the [160Tb]Terbium Complexes of the Bone-Targeting Ligands DOTP and BPPED

Abstract: The temperature-dependent adsorption on hydroxyapatite (HAP) of the Tb complexes of two macrocyclic DOTA-like ligands containing HAP-binding phosphonate groups was studied by a radiotracer method using 160Tb as the label. One ligand (DOTP) contains four separate phosphonate groups, while the second ligand (BPPED) contains a single bisphosphonate group coupled via a phosphinate spacer group. The equilibrium isotherms were fitted by models according to Langmuir, Freundlich, Langmuir-Freundlich, Toth, and Dubinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 29 publications
4
46
0
Order By: Relevance
“…Thus, Rill and al. [10] determined the thermodynamic parameters of hydroxyaptite interaction with some complexes containing functional molecules and showed that the process is endothermic and entropy-driven, due to the release of water molecules from the solubilized complexes as well as from the polar apatite surface upon adsorption. A similar dependence on temperature was previously reported for the uptake of phosphoproteins by hydroxyapatite [11].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Rill and al. [10] determined the thermodynamic parameters of hydroxyaptite interaction with some complexes containing functional molecules and showed that the process is endothermic and entropy-driven, due to the release of water molecules from the solubilized complexes as well as from the polar apatite surface upon adsorption. A similar dependence on temperature was previously reported for the uptake of phosphoproteins by hydroxyapatite [11].…”
Section: Resultsmentioning
confidence: 99%
“…High radiolabelling efficiencies (>98%) were reported for each ligand and it was noted that the 153 Sm/ 166 Ho-TRITP complexes bound to hydroxyapatite, which manifested in good bone uptake in corresponding biodistribution studies. 67 In an unrelated study, 160 Tb has been used for the physical study of the adsorption of lanthanide complexes to hydroxyapatite; 67 complexes of the phosphonate ligands DO3A BP and DOTP were studied. Adsorption was found to be very fast for both complexes, with the 160 Tb-DO3A BP complex showing a greater affinity for the hydroxyapatite surface than 160 Tb-DOTP, presumably due to the availability of the pendant bisphosphonate group.…”
Section: Macrocyclic Ligand Derivativesmentioning
confidence: 99%
“…9) and were originally developed by Parker and co-workers more than 20 years ago. 76 The original design of such systems was to address the chelation of 67 Ga and 111 In based radiopharmaceuticals (Table 1) However, more recent progress has shown that stable Ln(III) complexes can be achieved through functionalisation of the TACN framework with dipicolinate arms (Fig. 10).…”
Section: Macrocyclic Ligand Derivativesmentioning
confidence: 99%
See 2 more Smart Citations